Development and Characterization of Trihexyphenidyl Orodispersible Minitablets: A Challenge to Fill the Therapeutic Gap in Neuropediatrics - Camila Olivera; Oriana Boscolo; Cecilia Dobrecky; Claudia A. Ortega; Laura S. Favier; Valeria A. Cianchino; Sabrina Flor; Silvia Lucangioli (Pharmaceutics)
Background: Trihexyphenidyl (THP) has been widely used for over three decades as pediatric pharmacotherapy in patients affected by segmental and generalized dystonia. In order to achieve effective and safe pharmacotherapy for this population, new formulations are needed. Objective: The aim of this work is the development of trihexyphenidyl orodispersible minitablets (ODMTs) for pediatric use. Methods: Six different excipients were tested as diluents. The properties of powder mixtures were evaluated before direct compression and pharmacotechnical tests were performed on the final formulation. The determination of the API content, uniformity of dosage, and physicochemical stability studies were analyzed by an HPLC-UV method. Results: The developed ODMTs met pharmacopeia specifications for content, hardness, friability, disintegration, and dissolution tests. The physicochemical stability study performed over 18 months shows that API content remains within 90.0–110.0% at least for this period. Conclusions: These ODMTs will allow efficient, safe, and high-quality pharmacotherapy.